Model of Water Flow Infiltration Force in a Soil Mass - Teófilo-Salvador, Eduardo (REVISTA TERRA LATINOAMERICANA, 2025)
The flow of water in the soil generates processes that can be passive and active and manifest themselves in dif ferent ways. The objective was to propose a mathematical model to estimate the infiltration force of water in the soil in three components. It was based on formulations of Hydrology, Newton’s Law, and hydrogeology, and the water flow-soil mass system was identified through vertical, lateral, and superficial infiltration. To apply the formulations, reported data and experimental review of a multifunctional infiltrometer were used, and dry, saturated, and supersaturated soil masses were chosen. It has been obtained that the proposed model relates the variation of the infiltration force in direction, magnitude, and distribution, even for the same type of soil, the displacement is at dif ferent instantaneous speeds, due to the moisture content, porosity, hydraulic conductivity, and depth of the soil profile. The limitation is that no more multifunctional infiltrometers have been developed to apply the proposed model, but the results obtained can be associated with: i) if the vertical infiltration force predominates, there is greater ef fective infiltration as the first impulse of recharge, ii) if the lateral force predominates, the presence of soil instabilities, such as landslides, is possible, and iii) if the surface force predominates, the result is runof f or flooding on the soil.